Hypersplenism in a young girl: managed non-surgically - Batra, Tanvi; Gulati, Shipra; Gokhale, Vijayashree S.; Kakrani, Arjun Lal (International Journal of Research in Medical Sciences, 2017)
A 16-years-old female, non-alcoholic, presented with pain in left hypochondrium and distention of abdomen. Her USG Abdomen, portal vein doppler and CT abdomen revealed chronic thrombosis of intrahepatic portion of portal vein with multiple collaterals and gross splenomegaly suggestive of portal hypertension. Trans jugular liver biopsy showed no regeneration or fibrosis of liver. Endoscopy showed grade III oesophageal and gastric varices. Splenic artery embolisation was done for hypersplenism. Post procedure CT abdomen revealed large areas of splenic infarction-sequelae of splenic artery embolization.